FEASIBILITY ANALYSIS AND DEVELOPMENT STRATEGY OF SMOKED CATFISH BUSINESS FOR MSMES IN BANDAR LAMPUNG CITY: ANALISIS KELAYAKAN DAN STRATEGI PENGEMBANGAN USAHA IKAN LELE ASAP PADA UMKM DI KOTA BANDAR LAMPUNG - Witoko, Pindo; Rahayu, Sari; Mujahid, Muhammad; Lubis, Muhammad Zainuddin (Jurnal Teknologi Perikanan dan Kelautan, 2026)
Catfish is the most widely cultivated freshwater fish in Lampung Province, thus having great potential as a raw material for processing businesses, utilized by the Mina Nusantara MSMEs (micro, small, and medium enterprises) in Bandar Lampung City, as the region with the highest GDP (gross domestic product per capita) contribution from the processing industry sector. Mina Nusantara MSMEs still face limitations in business management, capital, marketing, and development strategies. This study aims to analyze business feasibility and formulate a development strategy for the Mina Nusantara smoked catfish business. The business feasibility analysis used net present value (NPV), internal rate of return (IRR), net benefit-to-cost (B/C) ratio, gross benefit-to-cost (B/C) ratio, and payback period (PP). The development strategy was carried out through an analysis of internal and external factors using the IFE and EFE matrices, by mapping the business position in the IFE matrix, formulating strategies using SWOT, and determining strategic priorities using QSPM. The results of the feasibility analysis indicate that the Mina Nusantara smoked catfish business is viable for continued operation and expansion. The feasibility analysis yielded an NPV of 294,327,358 IDR, an IRR of 58.75%, a gross B/C ratio of 1.22, a net B/C ratio of 2.85, and a payback period of one year and five months. The most effective implementation of Mina Nusantara's business development strategy is to strengthen accounting and administrative systems and to develop human resource capabilities and digital technology to support access to financing, improve business performance, strengthen collaboration, and expand the supplier network.